Percolación y lixiviación de nutrimentos en suelos bananeros al este del río Reventazón, Costa Rica. - Jorge Acón-Ho; Luis Alpízar-Oses; Rodolfo WingChing-Jones (Agronomía Mesoamericana, 2013)
El objetivo